7-Metalla-1, 4-diphosphanorbornadienes: cycloaddition of monovalent group 13 NacNac complexes to a stable 1, 4-diphosphinine. Issue 23 (16th May 2019) - Koner, Abhishek; Gabidullin, Bulat M.; Kelemen, Zsolt; Nyulászi, László; Nikonov, Georgii I.; Streubel, Rainer
Abstract : Monovalent group 13 NacNac complexes reacted as dienophiles with a tricyclic 1, 4-diphosphinine to furnish first examples of 7-metalla-1, 4-diphosphanorbornadienes via reversible [4 + 1]-cycloaddition reactions. Abstract : This work presents the first example of a dienophilic property of the monovalent group-13 NacNac complexes, which are well-known for their carbene-like reactivity, e.g., addition to multiple bonds, insertion into single bonds, and oxidative cleavage of some multiple bonds. In reactions with imidazole-2-thione based tricyclic 1, 4-diphospinine4, the monovalent compounds NacNacM (M = Al, Ga) showed dienophilic behaviour and produced the corresponding 7-metalla-1, 4-diphosphanorbornadienes (5–6 ), leaving the CS functionality of the imidazole-2-thione intact, while the NacNacIn complex did not show any reactivity because of unfavourable thermodynamics. DFT calculations revealed that for NacNacAl, the cycloaddition was kinetically more favoured (due to a small reaction barrier) than the oxidative cleavage of the CS functionality, despite the fact that the product of the CS bond addition has a somewhat higher stability. For NacNacGa, the cycloaddition reaction was both kinetically and thermodynamically favourable than the cleavage of CS. Furthermore, these reactions were found to be reversible in nature and diphosphinine4 showed a clear preference towards Al than towards Ga which reflects the better inclination of Ga to stay monovalent than be in the trivalent state.